Exfoliative cytology analysis from different sites of the body - Maharjan, Sushana; Ranabhat, Sabin; Tiwari, Mamata; Bhandari, Anita; Osti, Bidur Prasad; Neopane, Puja (Journal of Chitwan Medical College, 2017)
Background: Cytological study of body fluids a non-invasive, simple procedure, relatively inexpensive, and helps in faster reporting that has high population acceptance. The present study aims to determine the proportion of malignant and non malignant lesions. Methods: A total of 1129 specimens of exfoliative cytology were examined during the period over five years from year January 2011 to December 2016 at Department of Pathology at Chitwan Medical College Teaching Hospital, Nepal. The fluid received was centrifuged at 3000 revolutions per minute for five minutes. Smears were made from the sediment. Two to three slides were air dried and stained with Giemsa stain. One slide was immediately fixed in 95% alcohol and stained with Papanicolaou (Pap) stain for cytological evaluation. Results: Pleural fluid was most common specimen (49.3%) with peritoneal fluid (32%), pericardial fluid (1%), BAL (7.8%), CSF (4%), sputum (3.4%), synovial fluid (2%) and urine (0.5%) specimens. Male to female ratio was 1.33:1. Maximum cases belonged to age group of 50-69 years. Only (5.8%) 67 cases were neoplastic. The maximum cases of malignant neoplasm were detected in pericardial fluid and pleural fluid, each 21 (1.8%) cases, and 20 (1.7%) cases BAL. Malignant effusions were detected in 46 (4%) cases. Maximum malignant cases were adenocarcinoma (71.6%), followed by squamous cell carcinoma (20.8%). Conclusion: Exfoliative cytology should be suggested in all cases of effusion and suspected malignancies which helps in reaching at a particular diagnosis and aids in further management.